Too Much ‘Stuff’ and the Wrong Space: A Conceptual Framework of Material Possessions - Marco, Elena; Williams, Katie; Oliveira, Sonya (Interiority, 2020)
Space for living in new build houses in the UK is at premium and households have more stuff than ever before. The way this stuff is accommodated in dwellings can significantly affect residents’ quality of life and well-being. This paper presents a new conceptualisation of material possessions that could be of use to those involved in housing design. Three universal characteristics of material possessions; value, temporality and visibility are used to identify the space in the home that possessions might require. A conceptual framework that integrates these characteristics with spatial information about the interior of the home is developed. The paper argues that the conceptual framework could help designers, policymakers and house builders to better understand first the nature of material possessions, and second how those possessions could be accommodated in contemporary homes, ultimately supporting improved quality of life and wellbeing for households.